Comparison of age of first drink and age of first intoxication as predictors of substance use and mental health problems in adulthood. (1st January 2019) - Newton-Howes, Giles; Cook, Susan; Martin, Greg; Foulds, James A.; Boden, Joseph M.
Highlights: Age of First Intoxication, but not Drink, predict adult use disorder outcomes. Covariates reduce or nullify associative size; high quality cohorts are needed. Age of First Intoxication associated with individual, family and societal metrics. Abstract: Background: International public policy on age of first alcoholic drink (AFD) has emphasised the long-term benefits of delaying AFD. This study aimed to compare AFD to age of first intoxication (AFI) as predictors of substance use disorder and mental disorder outcomes in adulthood. Methods: Data were obtained from a longitudinal birth cohort in Christchurch, New Zealand. Participants were born in 1977. Analysis samples ranged from n = 1025 (age 18) to n = 962 (age 35). Measures of AFD and AFI were generated using parental- and self-report data collected from age 11. Outcomes at age 18–35 were alcohol quantity consumed, DSM-IV alcohol use disorder (AUD) and AUD symptoms, major depression, anxiety disorder, and nicotine, cannabis, and other illicit drug dependence. Covariate factors measured during childhood included family socioeconomic status, family functioning, parental alcohol-related attitudes/behaviours, and individual factors. Results: There was a significant unadjusted association between AFD and symptoms of AUD (p < .001) and nicotine dependence (p < .05) but not other outcomes. AFI was significantly (p < .05) associated with all outcomes. After adjustment for covariates, the association between AFD and outcomes was not statistically significant. Conversely, in adjusted models, statistically significant (p < .05) associations remained between AFI and all AUD and substance use disorder outcomes but not alcohol consumption or mental disorder outcomes. Conclusions: AFI was a more robust predictor of adult substance use disorder outcomes than AFD. Public health and policy interventions aimed at prevention of long term harms from alcohol should therefore focus on AFI rather than AFD.